PERAN ORIENTASI KEWIRAUSAHAAN DALAM MENCIPTAKAN KINERJA BISNIS - Mulyanto, Kukuh (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Entrepeneurship orientation has been acknowledged in literature andpractice as a vital element of economic and organizational growth, successand competitiveness and can be considered as a unique competitiveadvantage.The purpose of the paper is to provide a comprehensive analysis of the conceptof entrepeneurship orientation. Concluding, the paper suggests directions forfuture research.